New era for the coconut sector. What prospects for research? - Prades, A.; Salum, U.N.; Pioch, D. (EDP Sciences, 2016)
For years and years, the main output of the coconut sector on the international market was copra, crude coconut oil (CNO) and its derivatives. However, since approximately 10 years, we see new products so called “non-traditional” products entering global exchanges. The market growth of these products, mainly coconut water extracted from mature or immature nuts, virgin coconut oil (VCO) cold pressed from the fresh kernel, coconut sugar taken from the sap flowing out of the flower, is exponential. They benefit from the healthy, simple and natural image that is conveyed by the coconut tree in the subconscious minds of the consumers. The craze for this new products create also biggest expectative from the consumers towards the coconut stakeholders. This is why this article will also suggest some tracks of reflection for the research and expert’s communities, who would like to support this expansion, thus contributing to the future of the millions of small coconut farmer.